Acquired haemophilia A, concomitant acute myocardial infarction and urgent major surgery: How to successfully treat a critical patient with rpFVIII (Obizur®) - Zanon, Ezio; Pasca, Samantha; Spiezia, Luca; Poletto, Francesco; Gherardi, Simone; Simioni, Paolo (Thrombosis research, 2020)
Association of acute myocardial infarction (AMI) and acquired haemophilia A (AHA) is extremely rare, and very difficult to treat, if the patient then presents several serious comorbidities and must undergo an urgent major surgery, the correct choice of haemostatic therapy is essential to avoid potentially life-threatening adverse events for the patient. The recombinant porcine FVIII (rpFVIII) is considered, together with the bypassing agents, as first-line therapy for the AHA, but compared to these it presents a reduced thromboembolic risk which makes it safer in patients who already present at the onset of haemorrhagic event an underlying cardiovascular disease. Haemorrhagic and thrombotic events are always to be taken into consideration in the case of surgery, but in the case of patients with concomitant acquired haemophilia the risk of having serious bleeding has further increase. Today there have been no reports of surgeries carried out under Obizur® coverage. We are reporting the successful case of an elderly critical patient with acquired haemophilia A and concomitant myocardial infarction, treated with rpFVIII and in which an urgent major surgery under coverage of this dug was performed for the first time. •rpFVIII (Obizur®) is recognized as first-line therapy for AHA, together to bypassing agents, but its use is not so widespread•no cases of thrombosis due to rpFVII have been reported in the literature, unlike what happened for the bypassing agents•on these basis, rpFVIII can therefore be considered the best choice especially in elderly patients with severe comorbidities•surgery is an event with a high risk of bleeding, especially if the patient has a pre-existing coagulation disorder•ours is the first report in which an urgent major surgery under rpFVIII coverage was performed